Pengaruh Rom Exercise Dini Pada Pasien Post Operasi Fraktur Ekstremitas Bawah (Fraktur Femur Dan Fraktur Cruris) Terhadap Lama Hari Rawat Di Ruang Bedah Rsud Gambiran Kota Kediri - Yunanik Esmi Dwi Lestari (coba, 2014)
Fracture is a cutting of bone continuity. ORIF (Open Reduction and Internal Fixation) is one of therapy management from fracture. The lack of mobility to the post ORIF patient infact to recovery injury process cannot go on perfectly. Of course this condition will influence the length of patient treatment day in the hospital. Rehabilitation that can be done by nurse to the post ORIF patient is by early ROM Exercise. This objective research is to know the influence early ROM Exercise to post operation low fracture extremity patient (femur fracture and cruris fracture) to the length of treatment day in Surgery Room RSUD Gambiran Kediri City. Research design that is used is Pre- Experiment by approach Postest Only Control Group Design. The population is the post operation low extremity fracture patient (femur fracture and cruris fracture) who is treated in Surgery Room by 30 respondent sample taken by purposive sampling technique. The free variable is early ROM Exercise and bound variable is the length of treatment day post operation low fracture extremity patient (femur fracture and cruris fracture). The data is gotten by observation, clarified by ratio scale, analyzed by Independent T-test (experiment) with SPSS 16. Based on research result (out put result) is gotten that length of treatment day most of respondent that is done early ROM Exercise is 4 days, they are 10 respondent (67%) and almost a half of respondent who are not done early ROM Exercise is 6 days, they are 6 respondent (40%). Based on Independent T-test Experiment shown the big significance number is 0,000 < α = 0,05. Being concluded that there is influence early ROM Exercise to the post operation low extremity fracture patient (femur fracture and cruris fracture)to the length of treatment day in Surgery Room RSUD Gambiran Kediri City. Post ORIF patient needs being done early ROM Exercise so that blood circulation can be fluent, accelerate recovery wound healing process and reduce the length of treatment day.